Kidnap : face to fae with death - Ekhomu, Ona (Lagos, Nigeria School of Management and Security, 2014)
A life account of kidnap of Dr. Ona Ekhomu. He gives a graphic assessment of all the elements connected with kidnap. The book also provides an analysis of myriad incidences of kidnapping in Nigeria and an insight into the working of security networks in the country.
Includes bibliographical references and index.
oif 18/07/2018
Loans
Keywords: Kidnapping; Abduction; Terrorism; Nigeria